Awareness, Attitude, and Practice of Medical Students Towards Hepatitis B Virus Vaccine at University of Mosul, Iraq - Ruqaya Salih; Zaid Yassen; Anmar AL-Dewachi (Al-Anbar Medical Journal)
Background: Hepatitis B virus (HBV) infection is a common health problem; all over the world, around 300 million people have had chronic HBV infection in 2019. Healthcare staff and medical students are at four times greater risk of acquiring HBV infection than the general population.    Objective: To assess medical students' awareness, attitude, and practice towards the HBV vaccine.  Materials and methods: We selected a convenient sample of 300 students from Mosul Medical College, from different academic stages, and a cross-sectional study was conducted from May 1st, 2023, to September 30th, 2023. Data were collected through a direct interview using a special questionnaire form, then tabulated, and analyzed using Excel 2010 and SPSS software Version 24.   Results: The participants were mainly from the 4th, 5th, and 6th stages (82%), and a good percent of student’s awareness (96%) of HBV transmission via contaminated blood, with 73% knowing vertical transmission of the virus from pregnant mother to their fetus. For vaccination awareness, 89% of students agreed that vaccination should be given to health care workers and 75% knew that full immunization consists of 3 doses, 53% of students have received the HBV vaccine, 50% of them received full 3 doses and half of vaccinated students received it at 4th and 5th stage.  Around 90% of the non-vaccinated students don’t know when and where to get the vaccine.    Conclusion: Despite good knowledge of HBV transmission, control, and vaccination schedule; only half of the participants have received the vaccine. One of the most important causes for the non-receiving vaccine was a lack of knowledge about the time and place for receiving the vaccine.